HUBUNGAN TINGKAT STRES DENGAN SIKLUS MENSTRUASI PADA REMAJA PUTRI DI SMAN 5 PEKANBARU TAHUN 2019 - Rizka Angrainy; Penti Dora Yanti; Elvi Oktavia (Institut Kesehatan dan Teknologi Al Insyirah, 2020)
ABSTRACT menstrual cycle are a series of events that are complexly affecting each other and occur simultaneously. Menstrual cycle can be influenced by stress factors. Stress is a perception of a threat or from a shadow of displeaseru that moves, alerts or activates an organism. Based on data obtained from the department of education the city of pekanbaru, it is known that schools which have the highest number of girls at SMAN 5 pekanbaru with the highest number of 639 people, while classes X and XI total 395 people and obtain information 8 people claimed to experince menstrual cycles that are not normal and as many as 6 of them experienced symptoms of stress. The purpose of this study was to determine the relationship between stress levels and menstrual cycle in young women at SMAN 5 pekanbaru. This type of research is quantitative with cross sectional design. The population is all young women and a sample of 80 people, taken by stratified random sampling technique. Data analysis was performed univariately and bivariately. The results obtained bye the majority of respondents had a moderate stress level of 31 people (38.8%) and for the menstrual cycle variable obtained the majority of respondents had a short menstrual cycle of 33 people (41.2%). Chi sqaure test results obtained p.value=0.012 <0.05, which means there is a relationship between the level of stress with the menstrual cycle in girls in SMAN 5 pekanbaru in 2019. being input and learning materials that add insight and increase knowledge for students at SMAN 5 cities pekanbaru. Keywords: Stress, Menstrual Cycle Reference: 19 (2004-2017)